The role of oral history in interpreting a place - du Boulay, Alethea Blanche (Curtin University, 2015)
To understand the role of oral history in interpreting a place, oral history methodology was used to explore place from a cultural point of view and interpretation through the constructivist approach. Kalamunda, Western Australia, was used as the subject place for this research and a series of oral history interviews were conducted with members of the community. The research supports previous studies and asserts that oral history methodology has a key position in the interpretation of place.